Hubungan Antara Dukungan Sosial dengan Kesehatan Mental di Indonesia: Kajian Meta-Analisis - Diajeng Laily Hidayati; Eny Purwandari (Guidena)
Social support stands as a pivotal determinant influencing mental health outcomes. Over the past decade, numerous studies have been conducted in Indonesia to explore the relationship between social support and mental health. The aim of this study is to investigate the effect size of the relationship between social support and mental health within studies conducted in Indonesia. Employing a meta-analytical approach, studies spanning from 2012 to 2022 were scrutinized. Researchers search across diverse scholarly databases including Publish or Perish, Google Scholar, SINTA, Garuda Portal, and Moraref. Employing the keywords 'mental health' and 'social support,' 32 pertinent studies were assimilated into this metaanalysis. Collated data encompassed correlation test results and participant sample sizes. The analytical framework adopted the random effects model using the JASP application. Findings revealed a mean effect of -0.566 across the 32 studies, signifying a notable effect size of high social support on mental health. Studies exhibited no publication bias and displayed heterogeneous effect sizes. Given the relatively substantial correlation effect between social support and mental health, a predisposition toward higher levels of social support becomes imperative in averting mental health issues.